2019
DOI: 10.3390/acoustics1010012
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Prediction of Far-Field Combustion Noise from Aeronautical Engines

Abstract: A hybrid methodology combining a detailed Large Eddy Simulation of a combustion chamber sector, an analytical propagation model of the extracted acoustic and entropy waves at the combustor exit through the turbine stages, and a far-field acoustic propagation through a variable exhaust temperature field was shown to predict far-field combustion noise from helicopter and aircraft propulsion systems accurately for the first time. For the single-stream turboshaft engine, the validation was achieved from engine cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Therefore, operational noise has to be minimized [16,17]. In the case of aviation engines, the contribution of combustion noise is notable at full thrust during takeoff [18,19]. Even though advanced airfoils with porous trailing edges can reduce airfoil noise [20], combustion is still a notable part of the acoustic emission [21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, operational noise has to be minimized [16,17]. In the case of aviation engines, the contribution of combustion noise is notable at full thrust during takeoff [18,19]. Even though advanced airfoils with porous trailing edges can reduce airfoil noise [20], combustion is still a notable part of the acoustic emission [21].…”
Section: Introductionmentioning
confidence: 99%
“…They predicted the spectral distribution of sound pressure within the combustor with acceptable qualitative and quantitative agreement against measurements [23]. Another study predicted far-field combustion noise from helicopter and aircraft propulsion systems with LES of a combustion chamber sector, an analytical propagation model at the combustor exit, and a far-field acoustic propagation through a variable exhaust temperature [24]. The results of these researches reveal that the hybrid method is efficient in predicting combustion noise.…”
Section: Theoretical Formulation 21 Hybrid Methodsmentioning
confidence: 86%
“…(12) shows that the 1D-AM can consider only the effect of a uniform flow field on sound propagation, whereas the large temperature and velocity gradient fields in the axial and lateral regions of the load pipe are ignored. Many studies have shown that a velocity discontinuity in a moving medium will change the transmission and reflection characteristics of acoustic waves [20] [21], and a temperature discontinuity has a major effect on the propagation directivity of the transmitted waves [22] [23]. Therefore, ignoring the temperature and velocity gradient fields in the load pipe will generate significant errors in the solution of the acoustic parameters of loads.…”
Section: Functionsmentioning
confidence: 99%